Relation of Reduction of Antibodies against Hepatitis B Virus to Hepatocellular Carcinoma Recurrence in the Patients with Resolved Hepatitis B Virus Infection Following Direct-acting Antiviral Therapy for Hepatitis C Virus Infection - Joko, Kouji (Euroasian J Hepatogastroenterol, 2019)
BACKGROUND: A possible interaction of hepatitis viruses at cellular and molecular levels has been suggested. Eradication of hepatitis C virus (HCV) has been reported to induce activation of hepatitis B virus (HBV)-related liver diseases. MATERIALS AND METHODS: The present study examined association of HBV markers with recurrence of hepatocellular carcinoma (HCC) in patients with resolved HCV infection by direct-acting antiviral (DAA) therapy. In a patient pool of 378 patients with sustained virologic response (SVR) by DAA, the antibody to the hepatitis B surface antigen (anti-HBs), the antibody to the hepatitis B core antigen (anti-HBc), and HBV-DNA levels were estimated before and at the end of DAA therapy. These patients were HBsAg negative. Eighty-nine patients had a history of curative treatment of HCC by resection or radiofrequency ablation. A Cox proportional hazards model was used to identify risk factors for HCC recurrence, including the change ratio of the antibody against HBV proteins. RESULTS: Although 188 patients had resolved HBV infection, no patient showed HBV reactivation, but anti-HBs and anti-HBc levels decreased significantly. No significant difference in the HCC recurrence rate was evident between patients with and without resolved HBV infection. Changes of immune responses to HBV proteins did not affect HCC recurrence after DAA therapy for HCV infection in this cohort. CONCLUSION: The mechanisms underlying diverse roles of DAA-induced SVR of HCV on HBV kinetics need to be resolved in future. HOW TO CITE THIS ARTICLE: Joko K, Mashiba T, Ochi H, et al. Relation of Reduction of Antibodies against Hepatitis B Virus to Hepatocellular Carcinoma Recurrence in the Patients with Resolved Hepatitis B Virus Infection Following Direct-acting Antiviral Therapy for Hepatitis C Virus Infection. Euroasian J Hepato-Gastroenterol 2019;9(2):78–83.